Sjögren's syndrome myelopathy: Spinal cord involvement in Sjögren's syndrome might be a manifestation of neuromyelitis optica - Kim, S; Waters, P; Vincent, A; Kim, S; Kim, H; Hong, Y; Park, K; Min, J; Sung, J; Lee, K (2009)
Objective: To evaluate clinical characteristics, aquaporin (AQP)-4 antibody results, and probability of developing symptoms of neuromyelitis optica (NMO) in patients with Sjögren's syndrome myelopathy (SSM). Methods: We identified eight patients with spinal cord involvement from 112 patients with Sjögren's syndrome (SS) referred to the neurology department. The clinical characteristics and AQP-4 antibody status, based on immunoprecipitation of EGFP-tagged AQP-4, of the patients with SSM were assessed. Results: All patients with SSM had extensive spinal cord lesions, high mean annual relapse rates, and poor response to steroid treatment. Of the eight patients with SSM, seven patients satisfied the revised diagnostic criteria for NMO or showed positive results from AQP-4 antibody testing; one patient had incomplete follow-up. The clinical manifestations and AQP-4 autoantibody status of patients with SSM did not differ significantly from those of NMO patients without SS. Conclusion: All patients with SSM had poor prognosis with high mean annual relapse rates, and most seemed to have the clinical and immunological characteristics of NMO. Early aggressive immune therapies should be considered in patients with SSM irrespective of the presence or absence of optic neuritis.